2019
DOI: 10.1016/j.ctro.2019.04.016
|View full text |Cite|
|
Sign up to set email alerts
|

Heart and lung doses are independent predictors of overall survival in esophageal cancer after chemoradiotherapy

Abstract: Highlights Dosimetric parameters for the heart and lung are associated with overall survival in esophageal cancer patients. Heart and lung doses were associated with cardiac and pulmonary complications. Patients with cardiac and pulmonary complications are strongly correlated with survival outcomes. Dosimetric relationship with clinical outcomes are predictive for surgical and non-surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 34 publications
7
42
2
1
Order By: Relevance
“…In line with the large comprehensive research evaluating the association of cardiac dosimetric factors and the outcomes in esophageal cancer after CCRT with or without surgery [8], heart V20 was shown to in uence the survival of ESCC treated with de nitive CCRT in the present study. However, heart V5 and V10 which acted as independent prognostic factors in the current cohort were not found to independently in uence OS in the previously published report.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In line with the large comprehensive research evaluating the association of cardiac dosimetric factors and the outcomes in esophageal cancer after CCRT with or without surgery [8], heart V20 was shown to in uence the survival of ESCC treated with de nitive CCRT in the present study. However, heart V5 and V10 which acted as independent prognostic factors in the current cohort were not found to independently in uence OS in the previously published report.…”
Section: Discussionsupporting
confidence: 81%
“…However, heart V5 and V10 which acted as independent prognostic factors in the current cohort were not found to independently in uence OS in the previously published report. These discrepant results were possibly derived from the different cancer histologies and treatments between studies as the current cohort only reviewed ESCC patients receiving de nitive CCRT without surgery while the previous research included patients with adenocarcinoma and ESCC treated by CCRT with or without operation [8]. In addition, heart V30, V40, and V50 were not reported as independent predictors of OS in the present study because the statistical signi cance was not achieved in multivariate analytic models in which lung V5 was included.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Research evaluating radiation dosimetry demonstrates that the more conformal radiation dose distributions with IMRT have the potential to reduce radiation doses to the heart compared to conventional forms of radiation 14,[25][26][27][28] . Similarly, other retrospective analyses have found potential reductions in cardiovascular toxicity associated with IMRT compared to older radiation techniques 29,30 . Furthermore, a cancer registry study found that IMRT was associated with a decreased risk of cardiac mortality compared to conventional radiation 31 .…”
Section: Resultsmentioning
confidence: 90%
“…Radiotherapy remains a cornerstone of treatment for many cancers. Lung, esophageal, breast, and proximal gastric cancers still receive incidental radiation to the heart as part of curative intent or palliative care [1][2][3][4]. Contemporary and more sophisticated administration of thoracic radiotherapy and systemic immunotherapy have been effective in reducing cancer-related mortality and limiting exposure to the heart.…”
Section: Introductionmentioning
confidence: 99%